2019
DOI: 10.1111/jpi.12546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on the synthesis of estradiol and gene expression in pig granulosa cells

Abstract: The interaction of granulosa cells (GCs) with oocytes is important to regulate follicle development. The exogenous melatonin promoting the maturation of oocytes by GCs has been approved in pig, however, the transcriptome profile and the functions of the genes regulated by melatonin in GCs have not yet to be fully characterized. In this study, we found melatonin could stimulate the synthesis of estradiol in pig GCs. The RNA‐seq was used to explore the effects of melatonin on gene expression, a total of 89 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 108 publications
(114 reference statements)
1
24
0
Order By: Relevance
“…The reason may be that 500 mg/kg of quercetin is far beyond the effective range of quercetin to exert its role. Correspondingly, it has been demonstrated in other antioxidant studies that antioxidant effects are in a dose-dependent manner [28,29]. The present results will provide reference for the use of quercetin as a feed additive to protect broiler intestinal health.…”
Section: Discussionsupporting
confidence: 75%
“…The reason may be that 500 mg/kg of quercetin is far beyond the effective range of quercetin to exert its role. Correspondingly, it has been demonstrated in other antioxidant studies that antioxidant effects are in a dose-dependent manner [28,29]. The present results will provide reference for the use of quercetin as a feed additive to protect broiler intestinal health.…”
Section: Discussionsupporting
confidence: 75%
“…Treatment of mouse granulosa cells with 0.1, 1, 10, and 100 μM of melatonin revealed that the optimal concentration to inhibit palmitic acid-induced apoptosis was 10 μM, rather than 100 μM [11]. In pig granulosa cells, a low concentration (0.1 μM) of melatonin instead of the high concentration (10 μM) stimulates the synthesis of estradiol and produces differentially expressed genes, which are associated with regulation of cell proliferation, cell cycle, and anti-apoptosis [34]. These results support our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that 17β-estradiol (E2), the principal form of estrogens, is produced by adrenals and ovarian GCs and crucial for estrus cycle, ovarian development, follicular maturity, and ovulation (Baerwald et al, 2012;Herbison, 2020). E2 secretion is the most important function of female ovarian GCs, which also feedback regulates the transcriptome and the states (such as proliferation and apoptosis) of GCs in an autocrine manner (Ciesiolka et al, 2017;Liu et al, 2019). In recent years, E2 synthesis in female ovarian GCs has been proved to be regulated by a bunch of epigenetic regulation factors including miRNAs, circRNAs, and lncRNAs (Li et al, 2018a;Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%